2021
DOI: 10.1177/1467358421993882
|View full text |Cite
|
Sign up to set email alerts
|

Coastal and marine topics and destinations during the COVID-19 pandemic in Twitter's tourism hashtags

Abstract: Coastal and marine tourism offer various topics discussed within social media communication during a pandemic. The present study analysed the discussion topics in the popular Twitter's tourism hashtags during the COVID-19 crisis related to coastal and marine tourism. The objectives were to (i) determine the discussion topics, (ii) identify the discussion topics of greater hierarchy, and (iii) determine the tourist destinations discussed. The data were collected from Twitter between March and April 2020. A tota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 45 publications
(63 reference statements)
1
23
0
Order By: Relevance
“…Learning was analogous to studies presented by Ekonomou et al [26] and Rid et al [25]. Sun and beach and physical factors were similar to the findings in Carvache-Franco [27]; Carvache-Franco et al [31]; Ekonomou et al [26]; Güzel et al [30]; and Rid et al [25]. The motivation of authentic coastal experience has also been registered by Rid et al [25].…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Learning was analogous to studies presented by Ekonomou et al [26] and Rid et al [25]. Sun and beach and physical factors were similar to the findings in Carvache-Franco [27]; Carvache-Franco et al [31]; Ekonomou et al [26]; Güzel et al [30]; and Rid et al [25]. The motivation of authentic coastal experience has also been registered by Rid et al [25].…”
Section: Discussionsupporting
confidence: 86%
“…The motivation to find novelty has a positive impact on satisfaction, and transmission positively affects the loyalty of the visitor to the destination of the coastal and marine adventure tourism. In a worldwide study in the period of COVID-19, academics such as Carvache-Franco et al [31] identified two dimensions of coastal and marine tourism including "Escape", for the theme "travel" and "sun and beach". For the themes "beach", "sea", and "cruise" in this study, the tourism hashtags on Twitter were analyzed.…”
Section: Motivations To Visit Coastal and Marine Destinationsmentioning
confidence: 99%
“…This author found that fear of COVID-19 and perceived risk had a significant negative impact on attitude towards travel; however, social media had a significant positive effect. From this perspective, academics, such as Carvache-Franco et al [26], found two dimensions of coastal and marine tourism "escape," for the theme "travel" and "sun and beach," for the themes "beach," "sea," and "cruise" in a worldwide study using Twitter tourism hashtags during the COVID-19 pandemic.…”
Section: Motivations In Coastal Citiesmentioning
confidence: 99%
“…A few have focused on pollution [20,21], environmental education and teaching [22,23], fisheries [24], environmental issues [25,26]. Studies dealing directly with beach tourism have addressed social media [27], local tourism networks [28], one-day tours [29], and the carrying capacity of the beach [2]. New publications regarding the COVID-19 pandemic and coastal management are currently underway.…”
Section: Introductionmentioning
confidence: 99%